2001
DOI: 10.1603/0022-0493-94.4.942
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Sources and Mechanisms of Resistance in Crucifers for Control of Cabbage Maggot (Diptera: Anthomyiidae)

Abstract: The cabbage maggot, Delia radicum (L.) is an important insect pest of eruciferous crops in upstate New York. This species causes considerable damage to seedlings and young plants by feeding on roots and stems, resulting in plant stand loss and yield loss. Five crucifer accessions (Brassica oleracea variety italica L.,'Green Comet'; B. oleracea L.,'Rapid Cycling' [Crucifer Genetics Cooperative 3-1 ]; B. oleracea variety botrytis L., a standard cauliflower cultivar'Amazing'; B. carinata L.; and Sinapis alba L., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…The proportions of successfully developing larvae and pupae are commonly used to assess the level of antibiosis resistance to D. radicum (Finch and Ackley 1977;Ellis et al 1999;Jyoti et al 2001;Felkl et al 2005). In the field experiment we collected larvae and pupae from the soil around the root system.…”
Section: Parameters For Resistance Screensmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportions of successfully developing larvae and pupae are commonly used to assess the level of antibiosis resistance to D. radicum (Finch and Ackley 1977;Ellis et al 1999;Jyoti et al 2001;Felkl et al 2005). In the field experiment we collected larvae and pupae from the soil around the root system.…”
Section: Parameters For Resistance Screensmentioning
confidence: 99%
“…Firstly, it includes the possible effect of the plant on pupal mortality/development. Some researchers collected pupae and evaluated fly eclosion under artificial conditions (Jyoti et al 2001;Felkl et al 2005), which excluded the possible effect of the plant root environment on pupal survival. Felkl et al (2005) reported the fraction of flies that eclosed from pupae to range from 0.82 to 0.99 for the four tested B. fruticulosa accessions, and 0.85 for B. oleracea BOL2010-0437.…”
Section: Parameters For Resistance Screensmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some cultural controls such as crop rotation, row covers, and cultivation are used, current D. radicum control programs depend almost solely on chemical insecticides (Jyoti et al, 2001). The most commonly used pesticide for D. radicum control in the PaciWc Northwest is chlorpyrifos (Lorsban), an organophosphate.…”
mentioning
confidence: 99%